The importance of head control and its relevance in sports performance - Orlic, S. N.; Miskulin, A. (World Congress of Performance Analysis of Sport XII, 2018)
In the early motor development of a child, head control is a crucial component for achieving normal neuromotor control of movement. Achieving head control is necessary for accomplishing further motor activities. In most children, the development runs smoothly without any difficulties. Therefore, we are often unaware of the importance of the aspect of head control for further functioning. In children whose motor development is delayed or disrupted, head control is not established (on time). Getting the control of head movement is a very complex task, and if it is lacking - a physiotherapeutic guidance is of crucial importance. The aim of this paper is to stress the importance of establishing head contol in children. Head control is the crucial aspect of development, especially for children with motor disabilities but also for top athletes, with the aim of pointing out how important physiotherapeutic work is for achieving better quality control. Our contribution with this paper is to point out a functional approach to the motor development of a child and its connection with top athletes. Methods for establishing head control are just an initial point of achieving control of normal movement. Bobath neuro develop mental treatment for children is used for facilitation of motor development. This aproach includes a lot of activities in different body positions. An educated and experienced neuro physiotherapist will assess a child's initial status. Then the therapist chooses special techniques and undertakes specific procedures in order to encourage the child to achieve developmental progress. The important role of neurophysiotherapist is to facilitate early neuromotor development of the child, with the aim of achieving neuromotor control. A child who is not controlling the head, cannot achieve motor development nor can it walk independently. Athletes who have not mastered head control of the sport they are a part of. up to the mastery, cannot achieve significant sports results. In terms of motor control, we can compare head control of a child with head control of top athletes. Every athlete has to go through normal motor development in order to improve their skills to the top results. We must not forget the fact how important head control is. in achieving better sports results.